Evaluation of the Effectiveness of the Active Correction Exercises in Forward Head Posture in Young Adults - Arvind, Nehru; J., Muthukumaran (INTI International University, 2023)
Background: The forward head posture is terrible habitual posture of neck that is characterized by forward cervical vertebral translation and upper cervical vertebral hyperextension. Forward head posture for prolonged period of time puts extra strain on posterior aspects of cervical region including ligaments which alters scapular kinetics and kinematics. Objective: To evaluate and assess the efficiency of active correction exercises in forward head posture of young adults. Methodology: A Total 30 subjects with forward head posture were chosen using convenient sampling technique based on inclusion and exclusion criteria. Patients were split into two groups (Intervention group-15, Conventional group-15). The Intervention group received active correction exercises for Thoracic Spine, Sternocleidomastoid, Upper Trapezius, Lower Trapezius, Deep Cervical Flexors. Conventional group were not given any intervention. As an outcome measure, the APECS posture evaluation and correction system was utilized to assess pre- and post-test measurements. Result: The mean value of pre-test was 25.720 and the post-test was 39.140 for conventional group and the mean value of pre-test was 22.187 and the post test was 25.533 for intervention group. Conclusion: As a result of this finding, it has been concluded that exercises on correcting forward head posture were more effective than conventional group.